USING SOLIDWORKS FOR PROTOTYPING AERODYNAMIC STEERING DRIVES - KUSHNIRCHUK, ANDRIY; TKACHUK, VITALII; KARAZEY, VITALII; KHARZHEVSKYI, VIACHESLAV; MARCHENKO, MAKSYM (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work discusses the effective use of the Solidworks software for modeling complex mechanisms with moving elements of intricate shapes. The application of the program by designers in enterprises significantly increases the efficiency of the work of design bureaus and research and experimental departments. Development time is greatly reduced, and many analysis tools allow for the avoidance of errors. The use of Solidworks for creating 3D models, along with additive technologies for manufacturing these models, takes the creation of prototypes of complex steering drives to a qualitatively different level. To model such complex-shaped parts as ailerons, the Solidworks tool, "Section hood" was used, such a tool greatly simplifies modeling and allows you to achieve the desired shape of the model. The engine models were used in the Solidworks assembly and combined with the mating conditions with other components, this allowed to adjust the design "in the context of the assembly" to the actual dimensions of the engines. To analyze the correct movements of the drive elements, "mechanical couplings" with real gear ratios were installed on all gears. In this way, it was possible to fully analyze the movement of all drive elements, to determine their position during movement After the modeling and analysis process was completed, the prototype manufacturing process began, for which the FDM printing technology was chosen as the fastest, cheapest, but capable of reproducing complex shape details. CoPET plastic is chosen as the main material for printing, bearings are used for smooth rotation of drive elements, all axes of mechanisms are made of metal with the help of mechanical processing.The manufactured prototype turned out to be working, all movements are performed as intended in the modeling process, you can perform experiments and research with the obtained product to obtain the necessary results. The Solidworks software product allowed not only to fully simulate the steering drive, but also to avoid many errors thanks to the available analysis tools. The FDM printing technology made it possible to quickly create a prototype, provide all the intended functionality, the quality of the parts allows the drive to work correctly.